Years of schooling, human capital and the body mass index of European females - Giorgio Brunello; Daniele Fabbri; Margherita Fort (Institute for the Study of Labor (IZA), 2009)
We use the compulsory school reforms implemented in European countries after the II World War to investigate the causal effect of education on the Body Mass Index (BMI) and the incidence of overweight and obesity among European females. Our IV estimates suggest that years of schooling have a protective effect on BMI. The size of the estimated effect is not negligible but smaller than the one found in comparable recent work for the US. We depart from the current empirical literature in three main directions. First, we use a multi-country approach. Second, we complement the standard analysis of the causal impact of years of schooling on BMI with one relying on a broader measure of education, i.e. individual standardized cognitive tests, and show that the current focus in the literature on years of schooling as the measure of education is not misplaced. Last, we evaluate whether the current focus on conditional mean effects should be integrated with an approach which allows for heterogeneous responses to changes in compulsory education. Although our evidence based on quantile regressions is mixed, there is some indication that the protective effect of schooling does not increase monotonically from the lower to the upper quantile of the distribution of BMI. Rather, the marginal effect is stronger among overweight (but not obese) females than among females with BMI above 30.
Keywords: I12; I21; 330; Obesity; human capital; Europe; Gesundheitsrisiko; Bildungsniveau; Frauenbildung; Frauen; Europa